A statistical theory of target detection by pulsed radar - Marcum, J. (I.R.E. transactions on information theory, 1960)
This report presents data from which one may obtain the probability that a pulsed-type radar system will detect a given target at any range. This is in contrast to the usual method of obtaining radar range as a single number, which can be taken mathematically to imply that the probability of detection is zero at any range greater than this number, and certainty at any range less than this number. Three variables, which have so far received little quantitative attention in the subject of radar range, are introduced in the theory: l.The time taken to detect the target. 2.The average time interval between false alarms (false indications of targets). 3.The number of pulses integrated. It is shown briefly how the results for pulsed-type systems may be applied in the case of continuous-wave systems. Those concerned with systems analysis problems including radar performance may profitably use this work as one link in a chain involving several probabilities. For instance, the probability that a given aircraft will be detected at least once while flying any given path through a specified model radar network may be calculated using the data presented here as a basis, provided that additional probability data on such things as outage time etc., are available. The theory developed here does not take account of interference such as clutter or man-made static, but assumes only random noise at the receiver input. Also, an ideal type of electronic integrator and detector are assumed. Thus the results are the best that can be obtained under ideal conditions. It is not too difficult, however, to make reasonable assumptions which will permit application of the results to the currently available types of radar. The first part of this report is a restatement of known radar fundamentals and supplies continuity and background for what follows. The mathematical part of the theory is not contained herein, but will be issued subsequently as a Separate report(2a)